Teaching language from literature background: bringing the best of two worlds - Karim, Shuchi; Zaman, Tabassum (BRAC University, 2010)
Teaching English Foundation courses at the undergraduate level by teachers from literature background is a common scenario in the private universities of Bangladesh. Though there have been debates regarding the appropriateness and eligibility of literature teachers teaching language courses, one must recognize the fact that the basic problem is that of high demand and low supply of good language teachers. This paper addresses some of these much-debated issues, and also explores the possibilities of a more integrated teaching approach, which not only allows a literature-to-language shift but also makes the best use of the skills of teachers from a literature background, and investigates whether this exchange is salubrious enough to complement the purpose of language teaching.1 Because of the limited scope of this paper, we will limit our discussion within the boundaries of private universities and will base it on our own teaching experience within a similar background.